2016
DOI: 10.21608/jpp.2016.45385
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of High Temprature in Cabbage Plants Grown in Summer Season Using Some Nutrients, Antioxidants and Amino Acids As Foliar Application with Cold Water.

Abstract: Two field experiments were conducted during 2014 and 2015 summer seasons in the experimental farm of the Faculty of Agriculture at Moshtohor, Benha University to study the effects of spraying cabbage plants (Brassica oleracea var. capitata) cv. Balady with mineral nutrients i.e., potassium (K 2 O) at 2g/l, chelated calcium (Ca) at 2g/l, micronic sulphur (S) at 5g/l, boric acid at 100mg/l and antioxidants salicylic acid (SA) at 50mg/l, citric acid at 2g/l and amino acids at 2ml/l all of these materials are diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…The interaction between OS Cross cultivar and spraying with amino acid at 3 ml/l + NPK (15-15-15) fertilizer at 2 ml /l significantly increased head diameter and head circumferences, followed by the interaction between OS Cross cultivar and spraying with amino acid at 1.5 ml/l + NPK (15-15-15) fertilizer at 1 ml /l in both seasons. Mohamed and Zewail ( 2016) revealed that spraying with amino acids at 2 ml/l increased head diameter and circumference of cabbage cv Balady compared to control (spraying with normal water ).…”
Section: Head Qualitymentioning
confidence: 94%
See 3 more Smart Citations
“…The interaction between OS Cross cultivar and spraying with amino acid at 3 ml/l + NPK (15-15-15) fertilizer at 2 ml /l significantly increased head diameter and head circumferences, followed by the interaction between OS Cross cultivar and spraying with amino acid at 1.5 ml/l + NPK (15-15-15) fertilizer at 1 ml /l in both seasons. Mohamed and Zewail ( 2016) revealed that spraying with amino acids at 2 ml/l increased head diameter and circumference of cabbage cv Balady compared to control (spraying with normal water ).…”
Section: Head Qualitymentioning
confidence: 94%
“…two seasons (El-Afifi et al ,2014). Spraying with amino acids at2 ml/l increased head fresh weight of cabbage cv Balady compared to spraying with normal water (Mohamed and Zewail , 2016) .…”
Section: Head Yieldmentioning
confidence: 97%
See 2 more Smart Citations
“…Meanwhile, Sarkar et al (2007) found that foliar spraying of micronutrients Zn, Fe and Mn, significantly increased the yield of some vegetable crops. Foliar application of boron increased vegetative growth parameters, chemical constituents, yield and quality of cabbage (Devi et al, 2012;Mohamed and Zewail, 2016).…”
Section: Introductionmentioning
confidence: 99%